Whole body kinematics and knee moments that occur during an overhead catch and landing task in sport - Dempsey, A. R.; Elliott, B. C.; Munrod, B. J.; Steeled, J. R.; Lloyd, D. G. (Clinical Biomechanics, 2012)
Athletes suffering an anterior cruciate ligament injury tend to exhibit similar body postures that in sidestep cutting are associated with increased knee moments. This relationship, however, has not been investigated in landing. Catching a ball in different overhead positions may affect landing postures and knee joint moments. This study investigated these possible relationships. It was anticipated that some joint postures would be associated increased knee loads during the landing task.